Initiate of digital village for excellence service in archipelago area - Hidayaturrahman, Mohammad; Purwanto, Edy (Journal of Community Service and Empowerment, 2020)
Public services in Pagerungan Island / Village, Sapeken District, Sumenep Regency, East Java still use a manual system. This condition is troublesome for government officials and citizens who want to get services. On the other hand, the global world and the Indonesian government have launched Sustainable Development Goals (SDGs), the ninth goal is development based on technological progress. One of the efforts made to make this happen is by initiating a digital village (or Desa Digital/DEDI) in the archipelago. DEDI is a form of digital-based village administration service, using gadgets owned by residents connected to applications that are centralized in the village office. The pioneering of a digital village was carried out through socialization and focus group discussions (FGD) which were carried out with village government officials from the village head, village officials, to neighborhood associations. Equalizing perceptions and desires, so that the digital village began to be initiated through village meetings to be implemented starting in 2020. To make it work effectively, mentoring is carried out, related to making programs, modules, and transfer of technology to officers and community units). Digital villages are implemented using village funds in 2020 and 2021.